2022
DOI: 10.3390/ani12202742
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Non-Fermented and Fermented Chinese Chive Juice as an Alternative to Antibiotic Growth Promoters of Broilers

Abstract: The present study explores the application of CC juice as a suitable feed additive and alternative to conventional antibiotics. We performed a comparative study to investigate the effects of non-fermented and fermented CC juice on broiler productivity, meat quality, blood characteristics, intestinal characteristics, and microbiota associated with intestinal characteristics. A total of 800 one-day-old Ross 308 broiler chickens were randomly assigned to one of the four dietary treatment groups: (1) basal diet (n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 82 publications
0
9
0
2
Order By: Relevance
“…In agreement with this finding, Haque et al [15] also reported that the use of ciproflox and renamycin as AGP in broiler chicken diets elevated serum aspartate aminotransferase concentration. Similarly, Lee et al [16] also observed that aspartate aminotransferase concentration of broiler chickens was increased due to the use of enramycin as AGP. In another study, Erinle et al [17] also found that the use of bacitracin methylene disalicylate as AGP tended to increase serum aspartate aminotransferase concentration in broiler chickens.…”
Section: Resultsmentioning
confidence: 81%
“…In agreement with this finding, Haque et al [15] also reported that the use of ciproflox and renamycin as AGP in broiler chicken diets elevated serum aspartate aminotransferase concentration. Similarly, Lee et al [16] also observed that aspartate aminotransferase concentration of broiler chickens was increased due to the use of enramycin as AGP. In another study, Erinle et al [17] also found that the use of bacitracin methylene disalicylate as AGP tended to increase serum aspartate aminotransferase concentration in broiler chickens.…”
Section: Resultsmentioning
confidence: 81%
“…With the development of mass production of broilers, it has become an essential issue in improving the meat quality of broilers ( Mir et al, 2017 ). Meanwhile, meat quality also affects consumers' purchasing decisions and preferences ( Kirkpinar et al, 2014 ; Mir et al, 2017 ; Lee et al, 2022 ; Chang et al, 2023 ). Meat quality is usually reflected by pH, meat color, drip loss, cooking loss, shear force, and so on ( Scheier et al, 2014 ; Zhou et al, 2023 ; Mao et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, the high-density environment and some other unsuitable environmental conditions (such as pathogenic microorganism attack and nutrient deficiency) may cause immune stress or disease in broilers, which reduces the performance and meat quality. To alleviate these problems, breeding workers often add low doses of antibiotics in poultry production for a long time ( Huang et al, 2021 ; Lee et al, 2022 ; Lv et al, 2023 ). Antibiotics have made outstanding contributions to the healthy development of the livestock and poultry industry ( Tian et al, 2021 ; Zhou et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…There are several ways to improve plant nutrient availability, one of which is fermentation using probiotics [23]. Fermentation is a way to prevent food from spoiling and helps to improve the flavor, digestibility, nutritional content, and palatability of the substrate; in particular, it can enhance its biochemical properties, such as antioxidant and antibacterial activity [24]. Chinese chives (Allium tuberosum) fermentation through Lactobacillus plantarum improved functional substances such as propanoic acid, benzoylmesaconine, kaempferol, isorhamnetin, quercetin, hydroxystearic acid, and saponins in Chinese chives, and improved their ability to inhibit the avian influenza virus and pathogens [25].…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, studies on a comparison of physiological activity before and after the fermentation of plants and applications to livestock (pigs, poultry, daily cows, etc.) as a natural fermented feed additive have been conducted [24,[26][27][28].…”
Section: Introductionmentioning
confidence: 99%